Role of gemcitabine and cisplatin as neoadjuvant chemotherapy in muscle invasive bladder cancer: Experience over the last decade - Sunny Goel; Rahul J. Sinha; Ved Bhaskar; Ruchir Aeron; Ashish Sharma; Vishwajeet Singh (Asian Journal of Urology)
Objective: Neoadjuvant chemotherapy followed by radical cystectomy is considered the standard of care for patients with muscle invasive bladder cancer. In the last decade, interest in neoadjuvant chemotherapy has slowly shifted from methotrexate, vinblastine, doxorubicin and cisplatin regime to gemcitabine and cisplatin regime. There are many publications on gemcitabine and cisplatin regime in literature which cover different aspects of treatment. This review aims to summarise the findings published so far on gemcitabine and cisplatin regime and present it in a concise manner. Methods: A systematic literature review was conducted searching the PubMed® database in December 2016 using the medical subject heading (MeSH) with the terms gemcitabine, cisplatin, chemotherapy, muscle invasive bladder cancer, and neoadjuvant. All relevant studies were included and results were analysed. Results: A total of 13 studies were included which published between 2007 and 2015. These 13 studies comprised of 754 subjects suffering from muscle invasive bladder cancer. The proportion of male patients ranged from 60% to 86.4% and the median age ranged from 54.2 to 77.3 years in various studies. Complete pathological response (pT0) was seen in 30.0% of patients and pathological downstaging (<pT2) was seen in 48.67% of patients. Conclusion: As per latest guidelines, neoadjuvant chemotherapy is recommended for patients with muscle invasive bladder cancer. There is substantial pathological downstaging with low toxicity in patients of muscle invasive bladder cancer who receive neoadjuvant gemcitabine and cisplatin regime. Keywords: Muscle invasive bladder cancer, Gemcitabine, Cisplatin, Neoadjuvant chemotherapy, Radical cystectomy